Childhood Residential and Agricultural Pesticide Exposures in Relation to Adult-Onset Rheumatoid Arthritis in Women. Issue 2 (23rd August 2017) - Parks, Christine G; D'Aloisio, Aimee A; Sandler, Dale P
Abstract: Farming and pesticide exposure may influence risk of rheumatoid arthritis (RA); the role of early-life pesticide exposure is unknown. The Sister Study includes a US national cohort of women aged 35–74 years (enrolled 2004–2009); we examined childhood pesticide exposure in women in this cohort with adult-onset RA. Cases ( n = 424) were compared with 48, 919 noncases. Data included pesticide use at the longest childhood residence through age 14 years, farm residence of at least 12 months with agricultural pesticide exposure through age 18 years, and maternal farm experience. Odds ratios and 95% confidence intervals were adjusted for age, race or ethnicity, education, smoking, and childhood socioeconomic factors. Cases with RA reported more frequent and direct (personal) residential pesticide use in childhood (for infrequent/indirect pesticide use, odds ratio (OR) = 1.1; for frequent/direct use, OR = 1.8; P for trend = 0.013). Compared with women without residential farm history, odds of having RA increased for those reporting a childhood-only farm residence with personal exposure to pesticides used on crops (OR = 1.8, 95% confidence interval: 1.1, 2.9) or livestock (OR = 2.0, 95% confidence interval: 1.2, 3.3). Our findings suggest adult-onset RA may be related to childhood exposure to residential and agricultural pesticides, and support further investigations of lifetime pesticide use in RA.